Passage of human-origin influenza A virus in swine tracheal epithelial cells selects for adaptive mutations in the hemagglutinin gene - Jongsuk Mo; Lucas M. Ferreri; Ginger Geiger; Daniel R. Perez; Daniela S. Rajao (PLoS ONE, 2025)
Frequent spillover of influenza A viruses from humans to swine contributes to the increasing diversity of influenza viruses circulating in pigs. Although these events are common, little is known about the adaptation processes that take place when viruses jump between the two species. We examined the changes that occurred during serial passages of a reassortant H3N2 virus (VIC11pTRIG) containing human seasonal surface genes (Hemagglutinin and Neuraminidase) and a swine-adapted internal gene constellation in differentiated primary swine tracheal epithelial cells (pSTECs). The VIC11pTRIG reassortant virus was serially passaged 8 times in pSTECs and compared to a control swine-adapted strain (OH/04p) containing the same internal gene constellation. Viral RNA from passages 0 (inoculum), 1, 3, 4–8 were sequenced via next generation or Sanger sequencing. Hemagglutinin diversity was highest at passage 3. Two amino acid mutations in the Hemagglutinin protein (N165K and N216K) were fixed at passages 7 and 5, respectively. These changes were associated with increased fitness of the virus in pSTECs compared to the original parental strain. Our results suggest that the adaptation of human seasonal H3N2 to swine cells may lead to the selection of HA mutations located near the receptor binding site. These mutations may result in increased fitness of human-origin H3N2 strains to adapt in swine.